Transfusional Approach in Multi-Ethnic Sickle Cell Patients: Real-World Practice Data From a Multicenter Survey in Italy - Graziadei, Giovanna; De Franceschi, Lucia; Sainati, Laura; Venturelli, Donatella; Masera, Nicoletta; Bonomo, Piero; Vassanelli, Aurora; Casale, Maddalena; Lodi, Gianluca; Voi, Vincenzo; Rigano, Paolo; Pinto, Valeria Maria; et al. (Frontiers in Medicine, 2022)
Sickle cell disease (SCD) is a worldwide distributed hereditary red cell disorder characterized by recurrent acute vaso-occlusive crises (VOCs and anemia). It requires treatment such as hydroxycarbamide (HC) and/or different red blood cell (RBC) transfusion regimens to limit disease progression. Here, we report a retrospective study on 1,579 SCD patients (median age 23 years; 802 males/777 females) referring to 34 comprehensive Italian centers for hemoglobinopathies. Although we found a similar proportion of Caucasian (47.9%) and African (48.7%) patients, Italian SCD patients clustered into two distinct overall groups: children of African descent and adults of Caucasian descent. We found a subset of SCD patients requiring more intensive therapy with a combination of HC plus a chronic transfusion regimen, due to the partial failure of HC treatment alone in preventing or reducing sickle cell-related acute manifestations. Notably, we observed a higher use of acute transfusion approaches for SCD patients of African descent when compared to Caucasian subjects, which might be related to different factors such as (i) age of starting HC treatment; (ii) patients’ low social status; (ii) patients’ limited access to family practitioners; or (iii) discrimination. In our cohort, alloimmunization was documented in 135 patients (8.5%) and was more common in Caucasians (10.3%) than in Africans (6.6%). This is most likely related to differences in age and in the time of first exposure to RBC transfusion for SCD patients of Caucasian versus African descent. In addition, our study reinforces the importance of donor-recipient exact matching for ABO, Rhesus, and Kell antigen for RBC compatibility as a winning strategy to avoid or limit alloimmunization events that negatively impact the clinical management of SCD-related severe complications.